Model Peningkatan Motivasi Belajar Dengan Menggunakan Strategi Isa-Gallery Dalam Proses Pembelajaran Pendidikan Kewarganegaraan Pada Siswa Kelas VII B SMP Muhammadiyah 5 Surakarta Tahun Pelajaran 2015/2016 - Prabawati, Dhian Windari, Dra. Hj. Sri Gunarsi, SH., MH (2017)
The aim of this research is describe the formulation of the model deals, determine and refine models that can increase students' motivation in the learning process of Civic education in VII B class SMP Muhammadiyah 5 Surakarta period 2015/2016 by using ISA-GALLERY. The subject of implementing trial model is amount to 26 students of VII B class in SMP Muhammadiyah 5 Surakarta. The data of this research is collected through informants or interviewees, places and events ongoning learning activities. The data collection technique is using unstructured interview and observation method. The procedures in this study, there are four phases make the learning process, providing materials, pursuing a strategy of Information Search, then conduct a strategy Answer Gallery. This classroom action research is conducted through two test model is Information Search with Answer Gallery. To be expected, by using ISA-GALLERY strategy, students learning motivation during learning process of Civic in VII B class SMP Muhammadiyah 5 Surakarta period 2015/2016 can be increased by at least 80% of 26 students. The result of this research indicates that the level of students learning motivation in VII B class SMP Muhammadiyah 5 Surakarta period 2015/2016, specifically before trials model is 6 students or (23,1%). After testing the model is through learning model with strategies ISA-GALLERY test model I increased to 14 students or (54%) and the model II trials increased to 21 students or (81%).